Advanced glycation end products impair glucose‐induced insulin secretion from rat pancreatic β‐cells. Issue 2 (20th June 2013) - Hachiya, Hiroyuki; Miura, Yoshikazu; Inoue, Ken‐ichi; Park, Kyung Hwa; Takeuchi, Masayoshi; Kubota, Keiichi
Abstract Background Advanced glycation end products (AGEs) are derivative compounds generated from non‐enzymatic glycosylation and oxidation. In comparison with glucose‐derived AGEs (Glu‐AGEs), glyceraldehyde‐derived AGEs (Glycer‐AGEs) have stronger toxicity to living systems. In this study, we compared the effects of Glu‐AGE and Glycer‐AGE on insulin secretion. Method Rat pancreatic islets were isolated by collagenase digestion and primary‐cultured in the presence of 0.1 mg/ml bovine serum albumin (BSA) or 0.1 mg/ml Glu‐AGE or Glycer‐AGE‐albumin. After 24 h of culture, we performed an insulin secretion test and identified the defects by a battery of rescue experiments. Also, mRNA expression of genes associated with insulin secretion was measured. Results Insulin secretion induced by a high glucose concentration was 164.1 ± 6.0, 124.4 ± 4.4 (P < 0.05) and 119.8 ± 7.1 (P < 0.05) μU/3 islets/h in the presence of BSA, Glu‐AGE, and Glycer‐AGE, respectively. Inhibition of insulin secretion by Glu‐AGE or Glycer‐AGE was rescued by a high extracellular potassium concentration, tolbutamide and α‐ketoisocaproic acid, but not by glyceraldehyde, dihydroxacetone, methylpyruvate, glucagon‐like peptide‐1 and acetylcholine. Glu‐AGE or Glycer‐AGE reduced the expression of the malate dehydrogenase (Mdh1/2) gene, which plays a critical role in the nicotinamide adenine dinucleotide (NADH) shuttle. Conclusion Despite its reported cytotoxicity, the effects of Glycer‐AGE on insulin secretion are similar to those of Glu‐AGE.